Pembangunan Sistem Informasi Pelayanan dan Perawatan Penyakit Diabetes Mellitus berbasis Website (Studi Kasus: Klinik Griya Bromo Malang) - Riznin Ayustya Imandiena; Faizatul Amalia; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Diabetes Mellitus (DM) is a chronic disease of one types of non-contagious disease caused by a metabolic disorder due to the malfunctioning pancreas to produce insulin. Many diabetics who initially didn't know they had diabetes mellitus, and at the end the disease has spread to all organs and cause complications. It can't be denied, that this ignorance is based on the lack of knowledge and health facilities for diabetics. Griya Bromo Clinic is one of the clinics which specifically for diabetics. So far, the service process is still carried out with a paper based system managed by two admins. At first, this wasn't a problem, but the average number of patient who visited the clinic in a day reached 120 to 130 people. As one of the institutions that provide health services, clinic certainly requires the existence of an information system to improve their quality of service. Based on the existing problems, the result of requirement analysis is 33 functional requirement and 1 non-functional requirement. The next step is system design stage using UML, which can be used as a reference in system implementation with the PHP programming language and using CodeIgniter Framework. The final stage, system testing was carried out using black-box and white-box techniques that show 100% valid results for all the test cases, and on user acceptance testing show 100% valid results in 19 test cases. While in compatibility testing, the system runs well in 11 different browsers.